2012
DOI: 10.1136/bmjopen-2011-000809
|View full text |Cite
|
Sign up to set email alerts
|

How does comorbidity influence healthcare costs? A population-based cross-sectional study of depression, back pain and osteoarthritis

Abstract: ObjectivesTo analyse how comorbidity among patients with back pain, depression and osteoarthritis influences healthcare costs per patient. A special focus was made on the distribution of costs for primary healthcare compared with specialist care, hospital care and drugs.DesignPopulation-based cross-sectional study.SettingThe County of Östergötland, Sweden.PatientsData on diagnoses and healthcare costs for all 266 354 individuals between 20 and 75 years of age, who were residents of the County of Östergötland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…All patients in our study had a diagnosis of depression subsequent to a diagnosis of pain and we did not examine the health care costs associated with either condition alone. In a previous population-based study in Sweden, the average total health care costs (primary health care costs, hospital costs, and drug costs) per patient were higher for those with a diagnosis of both depression and back pain (SEK 46,909), compared with patients with a depression diagnosis (SEK 36,904) or a diagnosis of back pain (SEK 26,152) 30. Comorbidity of depression and pain had a negative interaction effect on health care costs, such that the costs were less than additive 30.…”
Section: Discussionmentioning
confidence: 86%
“…All patients in our study had a diagnosis of depression subsequent to a diagnosis of pain and we did not examine the health care costs associated with either condition alone. In a previous population-based study in Sweden, the average total health care costs (primary health care costs, hospital costs, and drug costs) per patient were higher for those with a diagnosis of both depression and back pain (SEK 46,909), compared with patients with a depression diagnosis (SEK 36,904) or a diagnosis of back pain (SEK 26,152) 30. Comorbidity of depression and pain had a negative interaction effect on health care costs, such that the costs were less than additive 30.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that comorbidities can influence hospitalization charges. 5,7 A higher comorbidity index > 2 comorbidities) also had a significant impact on the overall hospitalization cost (Fig. 5 and Table 7).…”
Section: Figmentioning
confidence: 99%
“…Other approaches have used multivariable models to model health expenditures and utilization by multiple individual conditions. 11,12 The limitation with this approach is that it assumes an additive relationship and does not account for the effect of possible nonlinear, non-additive co-occurrence of these conditions. Most importantly, given the reliance of most previous studies on administrative claims data alone, multimorbidity has been equated with multiple chronic conditions, without recognizing the simultaneous presence of functional limitations and geriatric syndromes, which are highly prevalent in older adults.…”
Section: Introductionmentioning
confidence: 99%